Cystic dilation of the common bile duct - Varela, Nelson B; Pravia, Carlos A (Cirugía del Uruguay, 2021)
A case of cystic dilatation of the main hile duct is presented. It was found in the course of an operation for acute cholecystitis. The diagnosis was possible after the operation through a cholecystocolangiogram. A review of the subjet and the various treatments proposed to treat this Condition are reported.